# 3t-7=5t+6t

## Simple and best practice solution for 3t-7=5t+6t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3t-7=5t+6t equation:

Simplifying 3t + -7 = 5t + 6t Reorder the terms: -7 + 3t = 5t + 6t Combine like terms: 5t + 6t = 11t -7 + 3t = 11t Solving -7 + 3t = 11t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-11t' to each side of the equation. -7 + 3t + -11t = 11t + -11t Combine like terms: 3t + -11t = -8t -7 + -8t = 11t + -11t Combine like terms: 11t + -11t = 0 -7 + -8t = 0 Add '7' to each side of the equation. -7 + 7 + -8t = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -8t = 0 + 7 -8t = 0 + 7 Combine like terms: 0 + 7 = 7 -8t = 7 Divide each side by '-8'. t = -0.875 Simplifying t = -0.875

### See similar equations:

| 50+7i=1 | | 10-4x=5-3x | | -161=7(1-4x) | | 10x^3+80= | | (17)+(-8)= | | 8x-9-(7-5x)= | | 324=(w)w+15 | | (-21)-(19)= | | 7x^2+9x-2=0 | | 7+4(y-3)=x | | 29+a=12 | | 2*1/2= | | -12(r-12)=408 | | -65=5(m+8) | | 12a-7a=2a+6 | | 88.00=0.40x+20 | | 6x^2-5x=2 | | 4(4-3x)=32-8(x+2) | | 15+(2x+3)(x-4)=2x^2-17 | | 3m-6n+2m-n= | | 8z-1(3+2z)=3z+1 | | 3(x+10)+4(x+20)+5x=185-3x | | (4x-1)(x+2)=4x | | (6x-5)(6x-5)=25 | | X^2+2x-7=16 | | -(1-4x)=p | | 6f-3=12f+4 | | 5x^2-25=4x^2+24 | | 7-21(x+3)=13-15(2x-5) | | 4t+9=6t+7 | | 3y-10=-14+y | | 3m-2=4m+1 | | 5y-11=-2+8y | | 3(-z+12)=4(15+d) | | 7y+11y=90 | | 8r-4=12r+6 | | -7y-12y=-144 | | -x^2+11x-10= | | x^2+6=5 | | -32+4x+x^2=0 | | 5(x-3)-7(6-x)+29=50-3(8-x) | | t^2+10ty+21y^2=0 | | 5j+2=4j-7 | | c^2-cy-56y^2=0 | | 28x^2+8x= | | -3x+8x=3x-2 | | 3[2x-(5x+2)]1=3x-9(x-3) | | 9x^8-36x^5+27x^7=0 | | 3(7+2w)=0.5(-2-10w) | | m^3n-16m^2n^2+63mn^3=0 | | 2x+5-7=-3 | | b^10+5b^9a-24b^8a^2=0 | | 7x^2-33x+20= | | 33.7-(1.5s+2.3)=3.4s-(0.4-5.7s) | | (a+b)x^2+(a+b)x-90(a+b)=0 | | 3y+5=4y+8 | | 6k+5=k+6 | | 9=2x^2-5 | | 3x-(-5x-x-3)=8x+(-5x-9) | | 2x+7-2+4x=8 | | 12+47=128 | | 5.40=1.90x+0.05 | | 4a=20-a | | 15=14a-5 | | 0.2x-8=0.6 |